2004
DOI: 10.1130/g19914.1
|View full text |Cite
|
Sign up to set email alerts
|

Holocene fault scarps near Tacoma, Washington, USA

Abstract: Airborne laser mapping confirms that Holocene active faults traverse the Puget Sound metropolitan area, northwestern continental United States. The mapping, which detects forest-floor relief of as little as 15 cm, reveals scarps along geophysical lineaments that separate areas of Holocene uplift and subsidence. Along one such line of scarps, we found that a fault warped the ground surface between A.D. 770 and 1160. This reverse fault, which projects through Tacoma, Washington, bounds the southern and western s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 17 publications
1
55
0
Order By: Relevance
“…Growth folding within the kink band beneath Case Inlet is consistent with geomorphic and paleoseismic observations made on the Catfish Lake fold scarp immediately to the west (Sherrod et al, , 2004. A 30-m long trench across the fold scarp (Fig.…”
Section: Data Acquisitionsupporting
confidence: 58%
See 3 more Smart Citations
“…Growth folding within the kink band beneath Case Inlet is consistent with geomorphic and paleoseismic observations made on the Catfish Lake fold scarp immediately to the west (Sherrod et al, , 2004. A 30-m long trench across the fold scarp (Fig.…”
Section: Data Acquisitionsupporting
confidence: 58%
“…2c; Johnson et al, 2004). The warping of the water bottom seen on the seismic reflection profile is similar in amplitude and wavelength to that at the Catfish Lake fold scarp to the west (Sherrod et al, , 2004, and it lies at the south edge of the uplifted terrace. The data therefore are consistent with latest Pleistocene or Holocene growth of the kink band in response to motion on an underlying fault (Fig.…”
Section: Data Acquisitionmentioning
confidence: 65%
See 2 more Smart Citations
“…Field investigation and analysis of other geological and geophysical data indicate that the linear features have a neotectonic origin, representing the surface expression of a seismically active fault. In areas with dense vegetation cover in the U.S. Pacific Northwest and Europe, 2-m resolution DEMs derived from LiDAR data have been successfully used for delineating earthquake surface ruptures [19][20][21]. Using 2-m and 3-m resolution DEMs derived from LiDAR data along portions of the Alpine and Hope faults in New Zealand, Langridge et al [22] found that the surface strike variations of the Alpine Fault are more variant than previously mapped, and that unprecedented views of the surface geomorphology of these active faults can be revealed by LiDAR data.…”
Section: Linear Geomorphic Markers Revealed By Lidarmentioning
confidence: 99%